ENGAGING SECONDARY SCHOOL STUDENTS IN EFL SPEAKING CLASSROOM THROUGH DIGITAL STORYTELLING - Azqiya, Navila Nuril (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2025)
This research aims to improve secondary school students' speaking skills in English as a Foreign Language (EFL) learning through the use of Digital Storytelling. The research employs a Classroom Action Research (CAR) design, involving 10 eighth grade students in a junior high school in Banyuwangi. Over four weeks, students participated in various stages of learning, including creating, presenting, and reflecting on digital stories. The data were collected from observation, interviews, and speaking tests. The qualitative data gathered from observation and interviewed were analyzed thematically where as data from speaking test were statistically analyzed. The findings reveal that implementing Digital Storytelling significantly enhanced students' speaking skills, such as fluency, pronunciation, and confidence. This method also fostered an engaging and interactive learning environment, helping students overcome their anxiety when speaking English. Moreover, students exhibited increased motivation, engagement, and creativity in storytelling. The process encouraged active participation and improved their ability to organize ideas coherently. Additionally, students demonstrated improvement in contextual vocabulary usage, grammar accuracy, and pronunciation. The results suggest that Digital Storytelling is an effective and innovative approach for enhancing students' speaking skills in EFL classrooms, making learning more meaningful and enjoyable.